ANALISIS PROSEDUR PEMBIAYAAN MUDHĀRABAH UNTUK MODAL USAHA STUDI KASUS PADA BANK MUAMALAT KANTOR CABANG PADALARANG BANDUNG BARAT - Cahyati, Lisna; Solihin, Dadin; Maryati (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2025)
The phenomenon that occurs in the community shows that some business actors are reluctant to apply for business capital loans to Islamic banks. This is due to the lack of public knowledge about financing procedures in Islamic banks, so they tend to choose other financial institutions that are considered easier and instant without considering future risks. This study aims to comprehensively analyze business capital financing procedures in Islamic banks to increase public understanding of sharia-based business capital financing. The focus of the research is directed at the Mudārabah financing procedure, which includes the stages of planning, implementation, process, and evaluation of its implementation. This study uses a qualitative approach with the researcher as the main instrument, assisted by interview guidelines and observation guidelines. Data were collected through interviews, observations, and documentation, and tested for validity with source triangulation techniques. Data analysis is carried out through four stages, namely data collection, data reduction, data presentation, and conclusion. The results of the study show that overall, the Mudhārabah financing procedure at Bank Muamalat Padalarang Branch Office is in accordance with existing theory, in line with the principles of sharia economics, and in accordance with the provisions of Islamic law.